2022
DOI: 10.1111/cas.15332
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass and obesity‐associated protein regulates arecoline‐exposed oral cancer immune response through programmed cell death‐ligand 1

Abstract: The high prevalence of oral squamous cell carcinoma (OSCC) in South Asia is associated with habitual areca nut chewing. Arecoline, a primary active carcinogen within areca nut extract, is known to promote OSCC pathological development. Dysregulation of N6‐methyladenosine (m6A) modification has begun to emerge as a significant contributor to cancer development and progression. However, the biological effects and molecular mechanisms of m6A modification in arecoline‐promoted OSCC malignance remain elusive. We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…Our recent papers showed that OSCC cell lines that had undergone chronic low-dose arecoline transformation (designated as SCC25-A and CAL27-A) had greater tumorigenic effects than the parental OSCC cell lines (SCC25 and CAL27) [ 12 ]. The RNA-seq transcriptome results revealed that METTL3 gene was among the significantly (fold change > 2 and p < 0.05) elevated genes when comparing CAL27-A to CAL27 ( Figure S1 ) [ 15 ]. To further confirm this result, the protein and mRNA levels of METTL3 in CAL27, CAL27-A, SCC25, and SCC25-A were measured.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent papers showed that OSCC cell lines that had undergone chronic low-dose arecoline transformation (designated as SCC25-A and CAL27-A) had greater tumorigenic effects than the parental OSCC cell lines (SCC25 and CAL27) [ 12 ]. The RNA-seq transcriptome results revealed that METTL3 gene was among the significantly (fold change > 2 and p < 0.05) elevated genes when comparing CAL27-A to CAL27 ( Figure S1 ) [ 15 ]. To further confirm this result, the protein and mRNA levels of METTL3 in CAL27, CAL27-A, SCC25, and SCC25-A were measured.…”
Section: Resultsmentioning
confidence: 99%
“…The m6A methyltransferase components primarily comprise three types of enzymes: “readers” (e.g., YT521-B homology (YTH) domain family proteins), “writers” (e.g., methyltransferase-like 3 (METTL3)), and “erasers” (e.g., alkB homologue 5 (ALKBH5)) [ 12 , 13 ]. Recent research has shown that several of these genes are implicated in the development of oral cancer [ 12 , 14 , 15 ]. The m6A modification gene’s role in arecoline-mediated oral cancer development and transformation, on the other hand, remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…The knockdown of FTO causes a decrease in PD-L1 mRNA stability and reduces PD-L1 expression on the surface of the cellular membrane. 76,77 Additionally, FTO also manipulates the expression of MYC and promotes PD-L1 expression in a transcriptional manner. 76,78 Remarkably, the methylation level can also influence the expression level of FTO.…”
Section: Erasermentioning
confidence: 99%
“…76,77 Additionally, FTO also manipulates the expression of MYC and promotes PD-L1 expression in a transcriptional manner. 76,78 Remarkably, the methylation level can also influence the expression level of FTO. The treatment of hypomethylating agents (HMA) promotes the m6A elimination, which also causes the up-regulation of FTO in a feedback pathway, rather than ALKBH5, METTL3 or METTL14, promoting the expression of PD-L1.…”
Section: Erasermentioning
confidence: 99%
See 1 more Smart Citation